Governance and Domestic Investment in Africa - Chimere Okechukwu Iheonu (European Journal of Government and Economics (EJGE), 2019)
The study empirically examined the impact of governance on domestic investment in 16 African countries with a balanced panel data set, between the years 2002 and 2015. The study employed six unbundled governance indicators from the World Bank, World Governance Indicators and constructed three bundled governance indicators using the Principal Component Analysis. The Driscoll and Kraay Fixed Effects model which accounts for serial correlation, groupwise heteroskedasticity and cross-sectional dependence were employed with empirical results revealing that all the indicators of governance positively and significantly influence domestic investment in Africa, except for government effectiveness which happens to be insignificant. Also, Voice/Accountability and the Control of Corruption exert more influence on domestic investment as indicated by their coefficient values. Furthermore, economic growth is also an important factor in explaining domestic investment in Africa. Policy recommendations are discussed.
Keywords: C01; E02; R5; 330; Governance; Domestic Investment; Africa; Principal Component Analysis; Fixed Effect Model